Indian Jewelry (New Mexico Magazine ?, 1984)
This article covers turquoise and silver jewelry crafting starting in the 1850's. It also covers how to care for and what to look for in Indian jewelry.
g
Master list item #: 23
File location is in the New Mexico file Cabinet
Keywords: Indian Jewelry; Indian Art; Turquoise; Silver; Jewelry Crafting; New Mexico; Arizona